How do Comparative Studies of Educational Achievement Inform us About Education Quality? - Leung, Frederick K. S. (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
In the past two decades, large-scale international comparative studies of educational achievement such as Trends in International Mathematics and Science Study (TIMSS), Progress in International Reading Literacy Study (PIRLS) and Programme for International Student Assessment (PISA) have attracted much attention in the education community and beyond. These international studies purport to allow policy makers around the world to gauge the knowledge and skills of students in their own countries in comparison with those in other countries, and thus help to improve the quality of education in the participating countries.